Analisis Perilaku Konsumtif pada Tren Pembelian Boneka Labubu di Kalangan Gen-Z - Putri, Nisrina Maulida; Ferlianti, Refa Adinda; Zuhri, Saifuddin (Komunika : Jurnal Ilmiah Komunikasi, 2024)
Consumption trends among Generation Z (Gen-Z) have undergone significant changes in recent years, particularly in the digital era dominated by social media. This study aims to analyze the consumptive behavior of Gen-Z toward Labubu figurines, which have gained popularity as exclusive collectible items. The research employs a qualitative approach through in-depth interviews with four informants. The focus includes the role of social media, psychological drivers such as Fear of Missing Out (FOMO), and the impact of communities on consumption behavior. The findings reveal that social media plays a pivotal role in spreading Labubu’s popularity, transforming it from a niche collector’s item into a global trend. The primary motivation for purchase is FOMO, which drives informants to participate in the trend to maintain social relevance. Collector communities also provide emotional support, encouraging informants to engage personally with Labubu as an expression of their lifestyle and identity. Responses to Labubu’s pricing vary, reflecting differences in preferences and individual tolerance for consumptive spending. Overall, Gen-Z’s consumptive behavior toward Labubu illustrates a complex interaction between social needs, social media influence, and product exclusivity. This phenomenon highlights how social media significantly shapes emotionally-driven, socially-connected, and aesthetically-oriented consumption patterns in the digital era. The study offers deep insights into shifting consumption patterns among Gen-Z, providing a robust foundation for further research on consumption trends in the technology-driven digital age.